Modeling the Vibrational Dynamics of Piezoelectric Actuator by System Identification Technique - Nurul Bahiah Mohd Noor; Mohd Ridzuan Ahmad (Institute of Advanced Engineering and Science, 2017)
Actuators based on smart materials such as piezoelectric actuators (PEAs) are widely used in many applications to transform electrical signal to mechanical signal and vice versa. However, the major drawbacks for these smart actuators are hysteresis nonlinear, creep and residual vibration. In this paper, PEAs are used for active vibration application. Therefore, a model of PEA must be established to control the vibration that occurs in the system. The frequencies of 1 Hz, 20 Hz and 50 Hz were tested on the PEAs. The results obtained from the experimental were used to develop transfer function model by employing system identiﬁcation technique. Meanwhile, the model validation was based on level of models ﬁtness to estimation data, mean squared error (MSE), ﬁnal prediction error (FPE) and correlation test. The experimental result showed that the displacement of the actuator is inversely proportional to the frequency. The following consequences caused the time response criteria at 50 Hz achieved smallest overshoot and fastest response of rise time and settling time.